Clinical and molecular genetic characterization of two female patients harboring the Xq27.3q28 deletion with different ratios of X chromosome inactivation. Issue 8 (19th June 2020) - Katoh, Kimiko; Aiba, Kaori; Fukushi, Daisuke; Yoshimura, Jun; Suzuki, Yasuyo; Mitsui, Jun; Morishita, Shinichi; Tuji, Shoji; Yamada, Kenichiro; Wakamatsu, Nobuaki
Abstract: A heterozygous deletion at Xq27.3q28 including FMR1, AFF2, and IDS causing intellectual disability and characteristic facial features is very rare in females, with only 10 patients having been reported. Here, we examined two female patients with different clinical features harboring the Xq27.3q28 deletion and determined the chromosomal breakpoints. Moreover, we assessed the X chromosome inactivation (XCI) in peripheral blood from both patients. Both patients had an almost overlapping deletion at Xq27.3q28, however, the more severe patient (Patient 1) showed skewed XCI of the normal X chromosome (79:21) whereas the milder patient (Patient 2) showed random XCI. Therefore, deletion at Xq27.3q28 critically affected brain development, and the ratio of XCI of the normal X chromosome greatly affected the clinical characteristics of patients with deletion at Xq27.3q28. As the chromosomal breakpoints were determined, we analyzed a change in chromatin domains termed topologically associated domains (TADs) using published Hi‐C data on the Xq27.3q28 region, and found that only patient 1 had a possibility of a drastic change in TADs. The altered chromatin topologies on the Xq27.3q28 region might affect the clinical features of patient 1 by changing the expression of genes just outside the deletion and/or the XCI establishment during embryogenesis resulting in skewed XCI.